2019
DOI: 10.22146/ijc.25702
|View full text |Cite
|
Sign up to set email alerts
|

Major Ions for Tracing Leachate Migration within Shallow Groundwater in the Vicinity of Municipal Landfill in Bantar Gebang - Bekasi

Abstract: Bantar Gebang landfill located in Bekasi regency is a biggest sanitary landfill in Indonesia which comes up some refusals from local people because of its bad impact on their environment. Major ion contents in leachate and fresh groundwater were investigated during the rainy and dry season to determine contamination by leachate released from Bantar Gebang and Sumur Batu landfill. Leachate contained high concentrations of all major ions that was mainly characterized as a NaKHCO3 water type. On the other hand, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Bantar Gebang poses many environmental problems besides landslides; for example, in September 2015, a fire consumed around four hectares due to hot weather and methane gas leakage from the MSW (Antara News, 2015). A study in 2019 found the groundwater in the vicinity of the Bantar Gebang landfill to be contaminated by 2% leachate (Indiyati et al, 2019).…”
Section: Location Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Bantar Gebang poses many environmental problems besides landslides; for example, in September 2015, a fire consumed around four hectares due to hot weather and methane gas leakage from the MSW (Antara News, 2015). A study in 2019 found the groundwater in the vicinity of the Bantar Gebang landfill to be contaminated by 2% leachate (Indiyati et al, 2019).…”
Section: Location Of the Studymentioning
confidence: 99%
“…Among the criteria are that: (1) the landfill has an impact on the environment; (2) the government cannot find other appropriate areas for landfills; and (3) the landfill handles non-hazardous waste (Indonesia Ministry of Public Works, 2013). The Bantar Gebang landfill certainly met some criteria, as indicated by its groundwater pollution, and the Jakarta Government has not found other areas for landfills yet (Indiyati et al, 2019). Furthermore, the regulation mentions that the soil-like material from landfill mining can be utilized in daily landfill cover, biofilters for leachate treatment, and compost for non-edible crops.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of the final disposal has had an impact on the environment around the Bantargebang final disposal [6]. The Bantargebang final disposal waste pile if simulated with the current situation will reach 36, 861, 653 tons in 2030.…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods used to validate hydrogeological conditions is an environmental isotope and hydrochemical analysis [1][2]4,[7][8][9]. Isotope composition in hydrological systems in nature are influenced by physical variables, namely air temperature, air pressure, humidity, geographical location, and altitude [10].…”
Section: ■ Introductionmentioning
confidence: 99%